MOTIVATION IN ORGANIZATIONS AND WORK STRESS MANAGEMENT IN IMPROVING HUMAN RESOURCE PERFORMANCE - Yosie Kristin Pandriyani; Hodiqotul Atfaliyah; Zakaria Syafei; Eka Sri Mulyani; Rijal Firdaos (Cakrawala Pedagogik, 2026)
Work motivation and stress management are two important factors that influence human resource performance in an organization. High levels of motivation can encourage individuals to work optimally, while good work stress management can maintain employee psychological balance so that performance remains productive. This study aims to analyze the role of organizational motivation and work stress management in improving human resource performance. The research method used is a qualitative approach with a systematic literature review (SLR) design. Research data was obtained by searching various scientific articles, books, and academic publications relevant to the topics of work motivation, work stress, and human resource performance in organizations. The data analysis process was carried out through the stages of identification, selection, evaluation, and synthesis of relevant literature. The results of the study indicate that work motivation has a significant influence on improving individual and organizational performance. Factors such as rewards, a conducive work environment, leadership support, and career development opportunities can increase employee motivation in carrying out their duties. On the other hand, poorly managed work stress can reduce productivity, increase levels of work fatigue, and impact the quality of performance. Therefore, organizations need to implement effective stress management strategies through workload management, creating a healthy work environment, and strengthening organizational support for employee well-being. This study shows that the integration between increasing work motivation and implementing effective stress management can be an important strategy in improving human resource performance and creating a productive and sustainable organization.